Penerapan Model Pembelajaran PBL Berbantuan Aplikasi Geogebra Untuk Meningkatkan Kemampuan Penalaran Matematis Siswa Kelas VIII - Melia Ariani Dewi; Sahat Saragih (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2023)
This research aims to: (1) improve students' mathematical reasoning abilities by applying the problem based learning model assisted by the Geogebra application in mathematics learning for class VIII students at SMP Negeri 3 Sunggal; (2) describe the process of completing student answers related to students' mathematical reasoning by applying the problem based learning model assisted by the Geogebra application. This research is Class Action Research. The subjects in this research were 28 students in class VIII of SMP Negeri 3 Sunggal. The results of the research show that: (1) students' mathematical reasoning can improve after learning by applying the problem based learning model assisted by the Geogebra application where the average student score in the cycle I reasoning ability test was 65.85, increasing to 85.39 in cycle II and classical completeness in the reasoning ability test in cycle I was 16 students (57.14%) increasing to 26 students (87.88%) in cycle II; (2) the process of students' answers in completing the mathematical reasoning ability test is in the good category, this can be seen from the students' answers which have been able to meet the indicators of mathematical reasoning ability. So it is concluded that the application of the Problem Based Learning learning model assisted by the Geogebra application can improve students' mathematical reasoning abilities.